No association between fear of hypoglycemia and blood glucose variability in type 1 diabetes: The cross-sectional VARDIA study - Saulnier, Pierre Jean; Briet, Claire; Gand, Elise; Chaillous, Lucy; Dubois, Severine; Bonnet, Fabrice; Leguerrier, Anne Marie; Fradet, Gérard; Delcourt Crespin, Ingrid; Kerlan, Veronique; Gouet, Didier; Perlemoine, Caroline; et al. (Journal of diabetes and its complications, 2019)
In type 1 diabetes (T1D), treatment efficacy is limited by the unpredictability of blood glucose results and glycemic variability (GV). Fear of Hypoglycemia (FOH) remains a major brake for insulin treatment optimization. We aimed to assess the association of GV with FOH in participants with T1D in an observational cross-sectional study performed in 9 French Diabetes Centres (NCT02790060). Participants were T1D for ≥5 years, aged 18–75 years, on stable insulin therapy for ≥3 months. The coefficient of variation (CV) of blood glucose and mean amplitude of glycemic excursions (MAGE) were used to assess GV from 7-point self-monitoring of blood glucose (SMBG). FOH was assessed using the validated French version of the Hypoglycemia Fear Survey-II (HFS-II) questionnaire. Among a total of 570 recruited participants, 298 were suitable for analysis: 46% women, 58% on continuous subcutaneous insulin infusion [CSII], mean age 49 ± 16 years, HbA1c 7.5 ± 0.9%, HFS-II score 67 ± 18 and 12% with recent history of severe hypoglycemia during the previous 6 months, mean CV 39.8 ± 9.7% and MAGE 119 ± 42 mg/dL. CV and MAGE did not significantly correlate with HFS-II score (R = −0.05;P = 0.457 and R = 0.08;P = 0.170). Participants with severe hypoglycemia in the previous 6 months had higher HFS scores. Participants with higher HFS scores presented more hypoglycemias during follow-up. FOH as determined using the HFS-II questionnaire was not associated with 7-point SMBG variability in participants with T1D, but was associated with a positive history of severe hypoglycemia. Higher FOH was associated with higher frequency of hypoglycemia during follow-up.